Establishing the tolerability to broiler chickens and laying hens of nonanoic acid at practical levels of use as a feed flavouring. Issue 2 (4th March 2022) - Bento, M. H. L.; Lewis, E. A.; Ramírez de Arellano, I.; Millán, C.; King, E.; Scott-Baird, E.; McGuire, P.; Richardson, K.
ABSTRACT: 1. The following experiments were conducted to evaluate the effects of nonanoic acid (NA) in broilers and laying hens, at practical levels as a flavouring in complete feed. 2. In the first experiment, 1100, one-day-old Ross 308 chicks, half male and female, were randomly assigned to 50 floor pens containing 22 chicks each. Chicks were fed one of five treatment diets containing either 0 (control), 100, 300, 500 or 1, 000 mg NA/kg complete feed for 42 days. 3. The NA treatment had no effect on ADFI, but there was a linear relationship with ADG and FCR. No differences were observed in blood parameters or tissue pathology among treatment groups. 4. In a second study, 150 Hyline hens aged 24 weeks old were randomly assigned to 50 pens containing three birds each. Laying hens were fed one of five treatment diets containing 0 (control), 100, 300, 500 or 1, 000 mg NA/kg complete feed for 56 days. 5. Treatment with NA has no effect on live weight, ADFI or egg production in laying hens, and there were no observed changes in tissue pathology. 6. The results supported the toleration of NA in broilers or layers at dietary levels of up to 1, 000 mg/kg.